Medical Image Compression Using Wavelets : Objective And Subjective Evaluations - Low , Yin Fen (2003)
In this project we would like to examine and compare the diffrerence in impact and quality of the wavelet functions (wavelets) to image quality for implementation in a digitized still medical image compression with different modalities.